2006
DOI: 10.1007/s00127-006-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

General health mediates the relationship between loneliness, life satisfaction and depression

Abstract: Even though less satisfied, and particularly lonelier, individuals are more likely to report higher levels of depression, this is only the case because both higher loneliness and life dissatisfaction are associated with poorer health. These results are discussed in terms of their implications for the diagnosis and treatment of mental health disorders in developing nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
82
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 29 publications
17
82
1
2
Order By: Relevance
“…A study on Malaysian medical students showed a positive relationship between life satisfaction and depression; but there were no reports on students' satisfaction with their field of study and their mental health status. (24) We highly suggest to measure the students' satisfaction by specific tools and evaluate its relationship with their mental health status in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study on Malaysian medical students showed a positive relationship between life satisfaction and depression; but there were no reports on students' satisfaction with their field of study and their mental health status. (24) We highly suggest to measure the students' satisfaction by specific tools and evaluate its relationship with their mental health status in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies into medical and dental student wellbeing have investigated the positive aspects of psychological well-being, such as life satisfaction and self-efficacy. Two studies have indicated an association between the positive and negative aspects (Swami et al 2007;Samaranayake & Fernando 2011). In fact, such investigations in Saudi Arabia are few and further studies are recommended (Inam 2007), especially during the current reforming period in Saudi medical education (Telmesani et al 2011).…”
Section: Practice Pointsmentioning
confidence: 99%
“…Santrock (2011) stated that adolescents who are rejected by their peers, with no close relationships and inadequate communication with friends, had increasing inclinations towards depression. Significant relationships between loneliness and depression were found in many studies (Hsu, Hailey & Range, 1987;Kim, 2001;Lasgaard, Goossens & Elklit, 2011;Rich & Scovel, 1987;Swami et al, 2007;Qualter, Brown, Munn & Rotenberg, 2010). According to the results of these studies in the relevant literature, lonely individuals are more likely to be depressed.…”
Section: Introductionmentioning
confidence: 95%